PERANCANGAN ULANG TATA LETAK FASILITAS PRODUKSI DI PT OSI ELECTRONICS - Turnip, Krismawan; Elsya Paskaria Loyda Tarigan (Computer Science and Industrial Engineering, 2024)
Presently, the facility layout at PT OSI Electronics Automotive Division is facing challenges. There is a significant distance between work stations, resulting in a longer material transfer distance and increased time for moving goods between work units. The objective of the performed research is to expedite the transfer of materials and propose recommendations for enhancing the layout of the firm's facilities. This will enable the company to decrease material handling expenses and minimise the distance required for material transfer. The stages conducted in this investigation encompass: Gathering data on the spatial separation of production lines, the quantity of workstations, and the dimensions of each production line. The acquired data was subsequently subjected to the Blocplan methodology for processing, followed by an examination of the optimisation outcomes, calculations, discussions, and ultimately drawing conclusions to determine the ultimate layout design. The most optimal plan for achieving efficiency and smoothness in the production process is layout 2, which is derived from software processing. Proposed schedule. The current configuration has a material handling distance of 68.46 metres, significantly shorter than the original layout's distance of 185.5 metres. Consequently, the overall distance for moving materials is reduced by 117.04 metres. The daily material handling cost for this proposed plan is IDR 1,288,760, which is lower than the material handling cost per metre in the initial layout, which was IDR 3,492,038. Consequently, the corporation can reduce its daily material handling expenses by IDR 2,203,278.